Association between Cathecol -O-Methyltransferase (COMT) Val 158 Met Polymorphisms and Psychosocial Stressors in Torajanese Schizophrenic Patients - Lisal T Sonny; Tanra Andi Jayalangkara; AndaSantiwati; Bahar Burhanuddin; Wahid Isra; Syamsuddin Saidah (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: TheTorajanese has a ritual tradition for the dead and marriage ceremonies from generation togeneration on a large-scale; this is one of the cultural factor that influences the evolution of genetic adaptation.Increased incidence of schizophrenia annually is often associated with Cathecol-O-Methyltransferase(COMT) Val 158 Met polymorphisms as one of the genes causing schizophrenia. This study was aimedto determine the association between Cathecol -O- Methyltrnasferase Val 158 Met polymorphisms andpsychosocial stressors with schizophrenia in Torajanese schizophrenia patients.Method: This was a quantitative study with a cross-sectional analytical description. There were 210 subjectsdivided equally into 3 groups, namely the Torajanese schizophrenia group with three subsequent generations(n = 70), normal Torajanese group (n = 70) and normal non-Torajanese group (n = 70). This study wasconducted at Hasanuddin University Hospital and its network. PCR and RFLP examination were used forCathecol-O-Methyltransferase (COMT) Val 158 Met polymorphism. Questionnaire was used to assess thepsychosocial stressors.Result: There was a significant difference in the distribution of genotypes between the Torajaneseschizophrenia group and the normal Torajanese group, between the normal Torajanese group and the thenormal non-Torajanese group (p <0.05). There were 3 genotypes in Cathecol -O-Methyltransferase (COMT)Val 158 Met polymorphisms in Torajanese, namely Val/Val, Val/Met and Met/Met; and for the 140 subjectsof the Torajanese, the amount of Val/Val genotypes was 104 (74.3 %) subjects, Val/Met genotype was 32(22.9%) subjects and Met/Met genotype was 4 (2.9%) subjects. It was found that 66 (47.1%) subjects hadpsychosocial stressors and 74 (52.9%) subjects didn’t have psychosocial stressor.Conclusion: There was a significant relationship between Cathecol -O-Methyltransferase (COMT) Val158 Met polymorphisms and Torajanese schizophrenia group. There was a significant association betweenpsychosocial stressors and Torajanese schizophrenia group. There was no significant difference in PANSSscores on the COMT Val 158 Met polymorphism genotypes.